Prevalence of Vitamin D Deficiency and its Predictors in the Portuguese Population: a Nationwide Population-Based Study - Duarte, C (2022)
Vitamin D deficiency is prevalent worldwide, but its prevalence is unknown in adult Portuguese population. In Portugal, 66% of adults present Vitamin D insufficiency/deficiency. Winter, living in Azores, older age, and obesity were the most important risk factors. It highlights the need of strategies to prevent vitamin D deficiency in Portugal. Objective: To estimate the prevalence and risk factors of vitamin D deficiency in the adult Portuguese population. Methods: Adults (≥ 18 years old) from the EpiReumaPt Study (2011-2013) were included. Standardized questionnaires on socio-demographic and lifestyle features were obtained. Serum 25-hydroxyvitamin D [25(OH)D] concentrations were evaluated using ADVIA Centaur VitD competitive immunoassay (Siemens Healthineers) in 2015-2017 as 25 (OH)D Level 0: ≤ 10 ng/mL; Level 1: 11-19 ng/mL; Level 2: 20-29 ng/mL, and Level 3: ≥ 30 ng/mL. Weighted multinomial regression analysis was conducted to evaluate the association between socio-demographic and lifestyle variables and vitamin D status. Results: Based on weighted analysis, the estimated prevalence of levels of 25(OH)D ≤ 10, < 20, and < 30 ng/mL was 21.2, 66.6, and 96.4%, respectively. The strongest independent predictors of serum 25 (OH)D ≤ 10 ng/mL were living in the Azores archipelagos (OR 9.39; 95%CI 1.27-69.6) and having the blood sample collection in winter (OR 18.53; 95%CI 7.83-43.87) or spring (11.55; 95%CI 5.18-25.74). Other significant predictors included older age (OR 5.65, 95%CI 2.08-15.35), obesity (OR 2.61; 95%CI 1.35-5.08), current smoking (OR 2.33; 95%CI 1.23-4.43), and female gender (OR 1.9, 95%CI 1.1-3.28). Conversely, physical exercise (OR 0.48, 95%CI 0.28-0.81) and occasional alcohol intake (OR 0.48, 95%CI 0.29-0.81) were associated with a lower risk of 25(OH)D ≤ 10 ng/mL. Conclusion: Vitamin D deficiency/insufficiency [25(OH)D < 20 ng/ml] is highly prevalent in Portugal, affecting > 60% of all Portuguese adults, with strong geographical and seasonal variation. This study highlights the need to critically assess the relevance of vitamin D deficiency as a public health problem and the urgent need for a wide and scientifically robust debate about the most appropriate interventions at the individual and societal levels.